Prosedur Pembiayaan Gadai Emas di PT. Bank Syariah KCP Medan Padang Bulan - Raisya Salsabila (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Gold pawn financing is an important service in the sharia financial industry. This research aims to examine gold pawning financing procedures at PT. Sharia Bank KCP Medan Padang Bulan. The research method used is a case study with a qualitative approach. Data was collected through observation, interviews and documentation studies. The gold pawning financing procedure at Bank Syariah KCP Medan Padang Bulan consists of several steps, including customer registration, gold appraisal, determining the financing value, signing the agreement, disbursing funds and storing the gold. This process is designed to provide easy and transparent financial access for customers who want to use gold as collateral. The research results show that the gold pawn financing procedure at Bank Syariah KCP Medan Padang Bulan is a structured and efficient process. With a good understanding of this procedure, customers can make optimal use of this service. It is hoped that this research can make a positive contribution to the development of gold pawn financing services at Sharia Banks and become a reference for further research in this field.